Why Physics Matters: A Student View on Building Better Healthcare Professionals in Croatia - Jelovica, Lejla; Erceg, Nataša; Pavelić, Sandra Kraljević; Jovanović, Željko; Miletić, Bojan (Education in Medicine Journal, 2026)
A comprehensive understanding of fundamental physical laws is essential for effectively using modern medical devices and comprehending the biological processes of organisms. This underscores the necessity of physics as a mandatory course in medical and healthcare studies. However, there is a lack of research regarding medical students’ motivation to learn physics and their awareness of its importance in healthcare, particularly among students in radiology and physiotherapy programmes. Therefore, the aim of this study is to assess students’ motivations for enrolling in healthcare programmes, their opinions about physics, and their perceived value of physics education for future career competencies. The sample comprised 157 undergraduate students from the physiotherapy and radiologic technology programmes at the Faculty of Health Studies, University of Rijeka, Croatia. Data were collected using a standardised questionnaire and analysed using the non-parametric Mann–Whitney U test and Kruskal–Wallis test. The research findings indicate that most students are enthusiastic about learning physics when they see its practical applications, especially in therapeutic and diagnostic procedures. Additionally, students are primarily motivated by a desire to help others, positive high school experiences, career aspirations, and family influence. Final-year students particularly recognise the significance of physics in diagnostics and therapies. Furthermore, professors’ professionalism and the curriculum’s relevance to future job skills are keymotivators. These findings can be used to develop diverse teaching strategies to enhance student interest, ultimately cultivating experts who can advance healthcare and improve disease diagnosis and treatment.